Reduced Expression of Nogo-A Leads to Motivational Deficits in Rats - Enkel, Thomas; Berger, Stefan M.; Schönig, Kai; Tews, Björn; Bartsch, Dusan (Frontiers in Behavioral Neuroscience, 2014)
Nogo-A is an important neurite growth-regulatory protein in the adult and developing nervous system. Mice lacking Nogo-A, or rats with neuronal Nogo-A deficiency, exhibit behavioral abnormalities such as impaired short-term memory, decreased prepulse inhibition and behavioral inflexibility. In the current study we extended the behavioral profile of the Nogo-A deficient rat line with respect to reward sensitivity and motivation and determined the concentrations of the monoamines dopamine and serotonin in the prefrontal cortex, dorsal striatum and nucleus accumbens. Using a limited access consumption task, we found similar intake of a sweet condensed milk solution following ad libitum or restricted feeding in wild-type and Nogo-A deficient rats, indicating normal reward sensitivity and translation of hunger into feeding behavior. When tested for motivation in a spontaneous progressive ratio task, Nogo-A rats exhibited lower break points and tended to have lower ‘highest completed ratios’. Further, under extinction conditions responding ceased substantially earlier in these rats. Finally, in the prefrontal cortex we found increased tissue levels of serotonin, while dopamine was unaltered. Dopamine and serotonin levels were also unaltered in the dorsal striatum and the nucleus accumbens. In summary, these results suggest a role for Nogo-A regulated processes in motivated behavior and related neurochemistry. The behavioral pattern observed resembles aspects of the negative symptomatology of schizophrenia.